2017
DOI: 10.5194/hess-21-4283-2017
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotopes of dissolved inorganic carbon reflect utilization of different carbon sources by microbial communities in two limestone aquifer assemblages

Abstract: Abstract. Isotopes of dissolved inorganic carbon (DIC) are used to indicate both transit times and biogeochemical evolution of groundwaters. These signals can be complicated in carbonate aquifers, as both abiotic (i.e., carbonate equilibria) and biotic factors influence the δ 13 C and 14 C of DIC. We applied a novel graphical method for tracking changes in the δ 13 C and 14 C of DIC in two distinct aquifer complexes identified in the Hainich Critical Zone Exploratory (CZE), a platform to study how water transp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Similar losses of aromatic constituents have been described for soils and rivers by other techniques (Creed et al, 2015;Klotzbücher et al, 2016). This implies that freshly decomposing materials can be traced by their contribution of aromatic-and phenolic-type formulae (Roth et al, 2013(Roth et al, , 2014(Roth et al, , 2016Nowak et al, 2017;Schwab et al, 2017). In short, Roth et al (2014) described several trends in a study including different sets of ecosystem samples.…”
Section: Retrieval Of Discriminating Information and Biogeochemical Tsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar losses of aromatic constituents have been described for soils and rivers by other techniques (Creed et al, 2015;Klotzbücher et al, 2016). This implies that freshly decomposing materials can be traced by their contribution of aromatic-and phenolic-type formulae (Roth et al, 2013(Roth et al, , 2014(Roth et al, , 2016Nowak et al, 2017;Schwab et al, 2017). In short, Roth et al (2014) described several trends in a study including different sets of ecosystem samples.…”
Section: Retrieval Of Discriminating Information and Biogeochemical Tsupporting
confidence: 61%
“…We found reproducible separation of a subset of these samples (water samples from forest soils, grassland soil, bogs, and rivers) on both instruments. This encompassed (a) differentiation of surface and soil water samples, which were paralleled by changes in pH and vegetation type (clusters A and B in Figure 5A; Roth et al, 2013Roth et al, , 2014, (b) retrieval of a depth trend found for grassland soils (JE-2-5 samples) including an increase in molecular similarity to river and marine samples with depth mainly due to vanishing aromatic-type formulae in the lower mass range (cluster C) (Roth et al, 2016), and (c) discrimination of anoxic (H5-3a) and oxic (H3-2b) aquifer environments (cluster D, Nowak et al, 2017;Schwab et al, 2017). Unique formulae of forest sites showed a higher aromaticity compared to unique formulae found in less acidic grassland sites, supporting the finding that aromatic signals < m/z 300 might be linked to fresh and less decomposed organic matter inputs (Roth et al, 2014(Roth et al, , 2016.…”
Section: Retrieval Of Discriminating Information and Biogeochemical Tmentioning
confidence: 97%
“…The medium 14 C-depleted wells H42, H43, and H52 share low-permeable rocks in laying and hanging strata (Lazar et al, 2019) and are therefore most likely cut off from direct surface-derived inputs, resulting in the moderate 14 C values of DOM in the water from these wells. While H53 had similar characteristics to H52 regarding the 14 C of inorganic carbon (Nowak et al, 2017) and major ion composition (Kohlhepp et al, 2017), DOM showed strong 14 C depletion of in H53 relative to H52. The strong 14 C depletion of DOM in H53 supported the indicated ecosystem compartmentalization by Lehmann and Totsche (2019), who described those zones as hydrogeologically isolated within the shallow groundwater flow system.…”
Section: Resultsmentioning
confidence: 90%
“…Consequently, limitation by labile organic carbon was most likely a key factor underlying the observed high relevance of anammox vs. denitrification in the oligotrophic carbonate-rock aquifers of the Hainich CZE. In fact, carbon isotope-based studies in the groundwater of wells H52 and H53 pointed to a tight internal cycling of carbon including oxidation of sedimentary old organic matter depleted in both 13 C and 14 C, and subsequent refixation of 13 C- and 14 C-depleted CO 2 by chemolithoautotrophs (Nowak et al, 2017 ). For the same groundwater sampling wells, Schwab et al ( 2017 ) found a strong depletion of phospholipid [3]- and [5]-ladderanes in 13 C (δ 13 C values ranging from –48.0 ± 10.5 to –45.9 ± 11.7%0), indicative of active CO 2 -fixation via the acetyl-CoA-pathway and characteristic of anammox bacteria (Schouten et al, 2004 ), confirming the substantial contribution of the anammox process to in situ autotrophic CO 2 -fixation.…”
Section: Discussionmentioning
confidence: 99%
“…For the same groundwater sampling wells, Schwab et al ( 2017 ) found a strong depletion of phospholipid [3]- and [5]-ladderanes in 13 C (δ 13 C values ranging from –48.0 ± 10.5 to –45.9 ± 11.7%0), indicative of active CO 2 -fixation via the acetyl-CoA-pathway and characteristic of anammox bacteria (Schouten et al, 2004 ), confirming the substantial contribution of the anammox process to in situ autotrophic CO 2 -fixation. Disconnection of these groundwater wells from surface-derived organic carbon input further appeared likely due to thick overlying soils, low infiltration potential, and low hydraulic conductivities with estimated groundwater travel times ranging from 295 to 587 years (Kohlhepp et al, 2016 ; Nowak et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%